PENGEMBANGAN TES DIAGNOSTIK PADA MATERI GERAK LURUS UNTUK SISWA SMA - Rakhmawati, Rakhmawati; Sutrisno, Leo; Maria S, Haratua Tiur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract the misconceptions experienced by students, and this research can be used This study aims to produce a good diagnostic test to explore students' misconceptions about straight motion material. The form of the research is a development research that is directed to produce a diagnostic test in the form of multiple choice with three choices of answers in the SMA straight motion material that is used to detect the students’ misconception. The limited scale trial was conducted in class X MIA 1 Senior High School 7 Pontianak. Whereas the largescale trials was conducted in class X MIA 3 and MIA 4 Senior High School 2 Pontianak and students of class X MIA 1 and MIA 2 Senior High School 8 Pontianak. The results of this study is in the form of diagnostic tests that meet the characteristics of a good diagnostic test with 18 questions which was developed based on the misconceptions experienced by the students with difficulty level 0.31-1.00, readability level 4.72, level of content’s validation 0.70 and reliability 0.80. The findings of this study are expected to help physics teachers to overcome as further research material for other students of physics education programs. Keywords: Diagnostic Test, Straight Motion